Limits on Constitutional Rights: The Marginal Role of Proportionality Analysis - Moon, Richard (2017)
Canada is often cited as one of the principal sources of proportionality analysis --- an approach to the determination of limits on constitutional rights that has been adopted in many jurisdictions. The two-step structure of constitutional rights adjudication is built on the idea that these rights are the basic conditions of individual autonomy or liberty that must be protected from the demands of collective welfare. At the first stage of the adjudication the court determines whether the restricted activity falls within the scope of the right. At the second stage, the court balances the right against the competing interest advanced by the restrictive law, to determine whether the restriction is justified. Yet few of these rights fit this individual liberty model and are better understood as social or relational in character – protecting different aspects of the individual’s interaction or connection with others in the community. If we recognize that most constitutional rights do not simply protect individual autonomy but instead protect different aspects of human flourishing or dignity within community then two things may follow. First there can be no single generic test for limits on rights. The form or character of “limitations” on these rights may differ in significant ways. Second, the two-steps of adjudication may often be difficult to separate or the separation may seem quite artificial. Many of the issues addressed by the courts will not fit easily into the two-step structure of analysis, because the “competing” interests are really different dimensions of a social relationship.
Keywords: Richard Moon